Role of Social Media in Enhancing Employee Performance - Sumayya, Ume (International Journal of Psychosocial Rehabilitation, 2020)
This research uses an exploratory approach to emphasize the importance of social media sites within corporations. It studies the intervening role of employee voice and employee engagement in the association between social media sites and employee performance specifically within the educational sector of Pakistan. Cross sectional data was collected from 250 faculty members teaching in various universities of Karachi, using simple random sampling. The derived hypotheses were tested through partial least square structural equation modelling method (PLS-SEM). The research outcomes statistically supported the influence of social media sites on employee performance using employee voice as a mediator. The research supported the fact that in today’s digital era employee voice and engagement are the key to enhance the worker’s productivity. The research findings can be used by academicians and human resource managers for formulating and evaluating their Human resource policies.